What influence does vaginal microbiota have on Human Papillomavirus infection? - Eleutério Junior, José; Vasconcelos, Rafael Pereira de; Oliveira, Marina Mara Sousa de; Eleutério, Renata Mírian Nunes; Gonçalves, Ana Katherine Silveira; Giraldo, Paulo César (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: The human body is colonized by trillions of microbial cells, called the microbiota. The microbiome is defined as microbial cells and their genomes. Vaginal microbiota, especially lactic acid bacteria (mainly Lactobacillus sp.), seem to play a critical role in the prevention of various urogenital diseases such as bacterial vaginosis, fungal infections, sexually transmitted diseases, urinary tract infections, and human papillomaviridae (HPV) infections. Changes in the vaginal microbiome contribute to the development of precancerous cervical lesions. Objective: To evaluate studies associating the vaginal microbiota with HPV, including the risk and persistence of infection and evolution to squamous intraepithelial lesions of the cervix. Methods: A systematic review was conducted based on articles published between September 2011 and September 2019, using the following keyword combinations: “HPV [All Fields] AND “microbiota” [MeSH Terms] OR “microbiota” [All Fields] OR “microbiome” [All Fields]).” The keyword search was performed in the MEDLINE, Latin American, and Caribbean Literature in Health Sciences (Lilacs), Cochrane Library, Highwire Stanford, and Embase databases. Results: In total, 239 original articles published between 2011 and 2019 were found in the researched databases on microbiome/microbiota and HPV. After exclusion, only six articles remained. Conclusion: There is a relationship between HPV and the cervicovaginal microbiota, but the mechanism of this influence cannot be specified.